To Study the Microbiological Profiling and its Antibiotics Pattern of Osteomyelitis in Patient Attending a Tertiary Care Centre - Faheem Ansari, Mohd; Shekhar Srivastava, Vinay; Kumar Verma, Rajesh; Afaq, Nashra; Rafeeq Ansari, Afzaal (Journal of Neonatal Surgery, 2025)
Background: When patients with bone infections, osteomyelitis continues to be the leading cause of morbidity. Osteomyelitis case management has become challenging due to the ongoing shift in the resistance pattern and the trend of organisms involved. In light of this, the current investigation sought to identify potential shifts in the patterns of antibiotic susceptibility and the bacteria implicated in osteomyelitis. Aim and Objective: To study the microbiological profiling and its antibiotics pattern of osteomyelitis in patient attending a tertiary care centre. Material and Methods: This was a Cross sectional study carried out in the Department of Orthopaedics and Department of Microbiology for a period of 12 months i.e, February 2024 to February 2025 at a tertiary care centre. A total of 100 cases were studied. Standard microbiological procedures were used to treat the samples, and antimicrobial testing was performed in accordance to the CLSI guidelines 2023. Results: There were 36 female patients and 64 male patients out of 100 cases; the average age of all the patients was 51.6±12.32 years. Among the patients, 64% had diabetes. Trauma is the most common risk factor for long bones (45%). Pseudomonas aeruginosa (21.2%) and Acinetobacter baumannii (16.7%) were the next most common pathogens found, after Staphylococcus aureus (24.2%). Gram-positive organisms tested completely sensitive to vancomycin, whereas Gram-negative bacteria were most sensitive to cefoperazone+sulbactam, piperacillin+tazobactam, meropenem, and imipenem. Conclusions: Methicillin-resistant Staphylococcus aureus and carbapenem-resistant gram-negative bacteria are major causes of osteomyelitis. Given the emergence of multidrug-resistant bacteria in osteomyelitis cases, cleanliness and tailored antibiotherapy should be prioritized.